Buffalo Horn Sign – A New Finding on MRI for Meniscal Bucket-Handle Tears - Pereira, Rafael R.; Cabral, João; Janeiro, João; Padín, José; Brito, Joaquim Soares do; Goes, Rodrigo A. (Revista Brasileira de Ortopedia, 2025)
To describe a new sign on magnetic resonance imaging (MRI) axial images of patients with bucket-handle meniscal tears.Of 610 consecutive patients with a surgical diagnosis of meniscal tear, those with a bucket-handle pattern were chosen, and 28 met the inclusion criteria. The most frequent mechanism was a twisting injury with or without a coronal stress (16 patients), and the injury was sports-related in 12 cases. All patients were symptomatic and had X-rays showing a preserved joint line. Next, their MRI examinations were analyzed.The buffalo horn pattern was found in 13 patients (46.4%), occurring in either the medial or the lateral meniscus. It was the 3rd most prevalent sign, after the fragment within the intercondylar notch (n = 21; 75.0%) and the absent bow tie sign (n = 17; 60.7%). We observed that it had a significant association with other signs of displaced meniscal handle. The sign was neither found on the healthy menisci, nor was affected by the occurrence of an anterior cruciate ligament tear.The buffalo horn is a new finding for displaced meniscal bucket-handle tears; it is easy to identify and relevant in the interpretation of axial MRI images. Its recognition is very important to determine the type of treatment and the surgical plan.
Keywords: diagnostic imaging; knee; magnetic resonance imaging; tibial meniscus injuries